2006
DOI: 10.1021/ac061109d
|View full text |Cite
|
Sign up to set email alerts
|

Method for Stabilizing Protein−Ligand Complexes in Nanoelectrospray Ionization Mass Spectrometry

Abstract: The interaction between the bovine pancrease trypsin (Tryp) and its competitive inhibitor benzamidine (1), in solution and the gas phase, is investigated using nanoflow electrospray ionization (nanoES) and Fourier transform ion cyclotron resonance mass spectrometry. In a recent study (Clark, S.M.; Konermann L. Anal. Chem. 2004, 76, 7077-7083), it was reported that the (Tryp + 1) complex could not be detected by ES-MS. Here, it is shown that, with gentle sampling conditions, it is possible to detect gaseous pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
137
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(147 citation statements)
references
References 27 publications
6
137
0
Order By: Relevance
“…Notably, the K a value, 1.2×10 5 M −1 , which was calculated from the measured abundance ratio (R) of ligand-bound to unbound Lg ions, is roughly 5-fold smaller than the reported affinity [21]. As described previously, collisional heating of gaseous ions can occur during accumulation in the rf hexapole in the FTICR mass spectrometer used for the present measurements [17]. Indeed, it was found that R (and K a ) increased as the accumulation time decreased.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…Notably, the K a value, 1.2×10 5 M −1 , which was calculated from the measured abundance ratio (R) of ligand-bound to unbound Lg ions, is roughly 5-fold smaller than the reported affinity [21]. As described previously, collisional heating of gaseous ions can occur during accumulation in the rf hexapole in the FTICR mass spectrometer used for the present measurements [17]. Indeed, it was found that R (and K a ) increased as the accumulation time decreased.…”
Section: Resultsmentioning
confidence: 60%
“…Recently, it was shown that the presence of imidazole, at high concentration (~10 mM), can protect protein-ligand complexes from in-source dissociation during ESI-MS analysis [17]. It was proposed that the stabilizing effect is due, at least in part, to enhanced evaporative cooling, which arises from the loss of multiple nonspecifically bound imidazole molecules from the gaseous protein-ligand complexes in the ion source [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanospray [34 -36] is often a gentle ionization method of allowing the use of less harsh conditions including a lower heated capillary temperature, the absence of heater gas, and a lower spray voltage while also providing high ionization efficiency for small-sample consumption. These advantages favor the application of nanospray to study protein conformation and noncovalent complexes [37][38][39].…”
mentioning
confidence: 99%